TO THE QUESTION OF METEOROLOGICAL INFORMATION SYNTHESIS - A. S. Spirin; A. L. Rybalkina (Научный вестник МГТУ ГА, 2016)
This article describes the possibility of creating an automated control system of processing meteorological information from multiple radar complexes